Meniscal repair: indications, techniques, and outcome - Pereira, H. (2016)
The current trend when dealing with meniscus tears is â preservation whenever possible.â This way, meniscal repair techniques have significantly developed in recent years. There have been advances in both surgical techniques (e.g., techniques for root tear repair) and related devices. However, anatomical knowledge is crucial, and learning curve time for any technique should be considered. Classification of tears, preoperative planning, and surgical training (including cadaver courses) are extremely important. This work aims to provide a comprehensive approach of the most frequent techniques and indications for meniscal repair. Moreover, it also describes a literature review focused on the expected outcome and possible complications.